Love's pursuit eaudiobook - Mitchell, Siri (Against All Expectations, 2009)
Set in 1640s Puritan Massachusetts, this "flawlessly crafted" (Booklist) historical novel by Christy Award finalist Siri Mitchell delivers a heart-wrenching tale of true love and triumphant grace. While Susannah awaits an overdue marriage proposal, a powerful villager takes a fancy to her. But after a dashing military captain comes to town, she's unprepared for the sinister turn her life soon takes. "A richly emotional, unforgettable story."-Booklist